Marketing Communications’ Trends on the Organic Food Market in Poland - Nestorowicz, Renata; Pilarczyk, Bogna (Studia Oeconomica Posnaniensia, 2018)
The organic food market in Poland is in a phase of dynamic development (10-20% yearly). On the supply and demand side its structure is changing. On the supply side, apart from fragmented entities, large production enterprises, offering until now only conventional food, are appearing more and more often. With their presence on the market, the financial resources and capabilities of marketing communications, in terms of scope and methods, have increased significantly. More money spent means also diversification and intensification of communication activities in this market. On the demand side, there is a growing interest in organic food among various consumer groups, as it fits into the trends of healthy eating, being fit and well (CBOS, 2016). Consumers who follow dietary fashion have become a significant market segment, next to existing consumers, purchasing organic food mainly for health reasons. That is why it is necessary to introduce changes in the processes and communication strategies in this market. Consumers are more and more often not only recipients of marketing messages, but also their creators. The aim of this paper is to present the evolution of conditions, tools and channels of marketing communications on the Polish organic food market, which have been taking place in the twenty-first century, as well as to indicate the directions of marketing communications’ development. These considerations will be conducted on the basis of market data and literature studies.